2021
DOI: 10.1097/hjh.0000000000003021
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific associations of brachial–ankle pulse wave velocity with adverse cardiac remodeling and long-term cardiovascular outcome

Abstract: Background: It remains unclear whether the cardiovascular consequences of arterial stiffness differ by sex. This study aimed to investigate the sex-specific association of brachialankle pulse wave velocity (baPWV) with adverse cardiac remodeling and cardiovascular outcome. Method:We studied 11 767 patients (57.6% men) with cardiovascular risk factors, whose baPWV was measured. The primary endpoint was composite cardiovascular events. Restricted cubic spline (RCS) analyses were performed to delineate the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In unadjusted comparisons, the prevalence of nondipping and reverse dipping increased in parallel with the decline in eGFR. In multivariate-adjusted logistic regression analysis, as compared with the referent quartile 4 of patients with the highest eGFR, the odds ratio (OR) for reverse dipping was 0.959 in quartile 3, 1.385 in quartile 2 and 1.685 in the quartile 1 [1]. A similar association was observed between the decreasing levels of eGFR and increasing likelihood for a nondipper with reverse-dipper BP pattern in 24-h ABPM.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In unadjusted comparisons, the prevalence of nondipping and reverse dipping increased in parallel with the decline in eGFR. In multivariate-adjusted logistic regression analysis, as compared with the referent quartile 4 of patients with the highest eGFR, the odds ratio (OR) for reverse dipping was 0.959 in quartile 3, 1.385 in quartile 2 and 1.685 in the quartile 1 [1]. A similar association was observed between the decreasing levels of eGFR and increasing likelihood for a nondipper with reverse-dipper BP pattern in 24-h ABPM.…”
supporting
confidence: 53%
“…A similar association was observed between the decreasing levels of eGFR and increasing likelihood for a nondipper with reverse-dipper BP pattern in 24-h ABPM. Using again patients with the highest eGFR as a reference category (quartile 4), the OR for nondipping with reverse dipping was 1.130, 1.345, and 1.422 for quartiles 3, 2 and 1 of eGFR, respectively [1]. In both occasions, there was a significant linear trend across quartiles, indicating that eGFR was an independent determinant of circadian BP variation in this large cohort of patients with preserved kidney function.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, the sex‐specific association of baPWV with adverse cardiac remodeling and the cardiovascular outcome was shown in a large population of 11,767 patients. The detrimental effects of baPWV on adverse cardiac remodeling and cardiovascular outcomes were stronger in women than in men 35 . Unfortunately, in our present study, the data of history of menopause were incomplete, so statistical analyses could not be carried out due to large missing values.…”
Section: Discussionmentioning
confidence: 92%
“…In a meta-analysis to determine if brachial-ankle PWV predicted CVD events (6.4 years follow up), sex differences were not reported [118]. However, a recent single site analysis of 11 767 patients (42% women) found that increased brachial-ankle PWV was more strongly associated with a higher risk of CVD events and death in women compared with men, after 3.6 years median follow up [119].…”
Section: Sex Differences In the Relationship Between Pressure And Flo...mentioning
confidence: 99%